2011 Third International Workshop on Quality of Multimedia Experience 2011
DOI: 10.1109/qomex.2011.6065689
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the acceptability of the audiovisual quality for a mobile video session based on objectively measured parameters

Abstract: Although Quality of Experience (QoE) plays a major role in the design and development of mobile applications and services, QoE assessment is still challenging, especially in real-life (so called `living lab') contexts. This paper presents results from an exploratory, interdisciplinary study on QoE and more specifically, on the acceptability of varying audiovisual qualities during video watching on a mobile device, in a realistic setting. The subjectively measured acceptability is modeled by means of a decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These models do not consider other influencing aspects, such as video resolution, and are dependent on the ability of knowing the video content types. In [12], a decision tree of audiovisual quality acceptance is determined by means of network type, transport protocol, video quality, and user watching behavior. The research made in living context, yet the subjective assessments for only two video qualities may not be enough to delegate the usage situations.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…These models do not consider other influencing aspects, such as video resolution, and are dependent on the ability of knowing the video content types. In [12], a decision tree of audiovisual quality acceptance is determined by means of network type, transport protocol, video quality, and user watching behavior. The research made in living context, yet the subjective assessments for only two video qualities may not be enough to delegate the usage situations.…”
Section: Related Workmentioning
confidence: 99%
“…The mapping process is to find the best-fit quality prediction model. There are many different approaches, including discriminant analysis [14], machine learning classification algorithm -decision tree [11,12], multiple linear regression [15], and non-linear regression [4,6]. Discriminant analysis and decision tree are suitable for classifying groups, such as acceptable or unacceptable, whereas linear and non-linear regression are appropriate for calculating an index, such as acceptability and MOS.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…They varied codec rates to create eight quality levels and found that mobile device users will deem multimedia quality acceptable differently on different devices. Research has been done [10] using mobile devices in "living labs"-letting experiment participants use a mobile device during their daily routine. Delivery of multimedia content to a mobile phone using Digital Video Broadcasting for Handhelds (DVB-H) was tested in the context of a train station, a bus, and a café in [11].…”
Section: Related Workmentioning
confidence: 99%